Proteomic analysis of the molecular response of Raji cells to maslinic acid treatment - Yeo, Chew Chieng (2012)
Maslinic acid a natural pentacyclic tritemene has been shown to inhibit growth and induce apoptosis in some tumour cell lines We studied the molecular response of Raji cells towards maslinic acid treatment A proteorrscs approach was employed to identify the target proteins Seventeen differentially expressed proteins including those involved in MIA replication microtubule filament assembly. nucleo-cytoplasmic trafficking cell signaling. energy metabolism and cytoskeletal organization were identified by MALDI TOE TOF MS The down-regulation of stathmin Ran GTPase activating protein-I (RanI3P1) and microtubule associated protein RPrE13 family member I (E131) were confirmed by Western blotting The study of the effect of maslinic acid on Raji cell cycle regulation showed that it induced a G1 cell cycle arrest The differential proteomic changes in maslinic acid-treated Rajl cells demonstrated that it also inhibited expression of dUTPase and stathmin which are known to induce early S and G2 cell cycle arrests The mechanism of maslinic acid-induced cell cycle arrest may be mediated by inhibiting cyclin Dl expression and enhancing the levels of cell cycle-dependent kmase (CDK) inhibitor p21 protein. Maslinic acid suppressed nuclear factor-kappa B INF-x13) activity which is known to stimulate expression of anti-apoptotic and cell cycle regulatory gene products. These results suggest that maslinic acid affects multiple signaling molecules and inhibits fundamental pathways regulating cell growth and survival in Raji cells 2011 Elsevier GmbH All rights reserved